Pharmacokinetics, in-situ absorption and protein binding studies of a new neuroleptic agent centbutindole in rats - Issar M.; Singh S.K.; Mishra B.; Gupta R.C. (My University, 2025)
The present study reports the absorption kinetics, plasma protein binding and pharmacokinetic profile of the centbutindole (I) after i. v. and oral dosing in rats. In addition, an in-situ absorption study was carried out using a closed-loop technique at pH 2.6 and 7.4. The rate of absorption at pH 2.6 was 5-fold less compared to that observed at pH 7.4. In-vitro and in-vivo protein binding (ultra filtration technique) was independent of substrate concentration over a range of 1.25-10.0 μg/ml. Pharmacokinetic parameters of I were determined in male rats after administering a single 4 mg/kg oral dose and 2 mg/kg intravenous dose. The peak serum concentration of I was found to be 50.1 ng/ml at 30 min after oral administration followed by a secondary Cmax of 43.2 ng/ml at 180 min. For the hydroxy metabolite (II), a Cmax of 6.4 ng/ml was measured at 360 min after oral administration of I. After oral dosing an irregular concentration-time profile with secondary peaks was observed for both I and II. The terminal half-lives for I and II after oral dosing were 163 and 263 min, respectively. After intravenous dosing, the levels of I decreased biexponentially with a distribution (t1/2 α) and elimination (t1/2 β) half-lives of 5.7 and 128 min, respectively. Comparison of the AUC after oral and intravenous dosing of I indicates that only about 24% of the oral dose reaches the systemic circulation. The limited bioavailability can either be due to the poor solubility of the compound and/or extensive first pass metabolism in the gastrointestinal (GI) tract. Co-administration of polyethylene glycol (PEG) at oral dosing improves solubilization and increases bioavailability. © 2003 Elsevier Science B.V. All rights reserved.